Three-dimensional atom localization by laser fields in a four-level tripod system - Vladimir S. Ivanov; Yuri V. Rozhdestvensky; Kalle-Antti Suominen (AMER PHYSICAL SOC, 2022)
We present a scheme for high-precision three-dimensional (3D) localization by the measurement of the atomic-level population. The scheme is applied to a four-level tripod-type atom coupled by three strong standing waves and a probe running wave. As a result, the atom can be localized in volumes that are substantially smaller than a cubic optical wavelength, which is achieved by the increase of standing-wave intensities. The upper-level distribution depends crucially on the atom-field coupling and it forms 3D periodic structures composed of spheres, hourglasses, bowls, donuts, or deformed barrels.